2022
DOI: 10.1002/ecs2.3859
|View full text |Cite
|
Sign up to set email alerts
|

Climate change influences foliar nutrition and metabolism of red maple (Acer rubrum) trees in a northern hardwood forest

Abstract: change influences foliar nutrition and metabolism of red maple (Acer rubrum) trees in a northern hardwood forest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
(173 reference statements)
0
2
0
Order By: Relevance
“…Some examples of such studies are 1) soil-based N supplementation of the mixedhardwood forest at Harvard Forest, MA affected both nutrient and metabolic profiles of red pine, black and red oak, and red maple trees (Minocha et al, 2000;Bauer et al, 2004;Minocha et al, 2015b); 2) Al toxicity originating from acidic deposition affected soil Al/Ca ratios and homeostatic balance in red spruce and sugar maple tissues in Northeast New England (Minocha et al, 1997;Wargo et al, 2002); 3) elevation-dependent changes occurring simultaneously in cellular soluble nutrients and metabolites were demonstrated in tree species growing in different countries (Minocha et al, 2010;Minocha et al, 2021). Elevation levels are known to be related to air pollution levels (higher elevations are more exposed to acidic deposition); 4) Climate change also influences foliar nutrition and metabolism simultaneously as was shown in red maple (Acer rubrum) trees exposed to soil warming with or without induced freeze-thaw cycles in a northern hardwood forest (Blagden et al, 2022); and 5) Rhizoctonia solani's damage to sugar beet increased in the presence of Leuconostoc mesenteroides as revealed by altered roots nutrient and metabolite levels in the infected roots (Majumdar et al, 2022). These authors suggested a common role of inorganic nutrients and primary metabolism in all host-plant fungal and bacterial pathogens besides the wellknown role of unique pathways and genes in the pathogens towards maintaining successful pathogenesis and the development of disease symptoms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some examples of such studies are 1) soil-based N supplementation of the mixedhardwood forest at Harvard Forest, MA affected both nutrient and metabolic profiles of red pine, black and red oak, and red maple trees (Minocha et al, 2000;Bauer et al, 2004;Minocha et al, 2015b); 2) Al toxicity originating from acidic deposition affected soil Al/Ca ratios and homeostatic balance in red spruce and sugar maple tissues in Northeast New England (Minocha et al, 1997;Wargo et al, 2002); 3) elevation-dependent changes occurring simultaneously in cellular soluble nutrients and metabolites were demonstrated in tree species growing in different countries (Minocha et al, 2010;Minocha et al, 2021). Elevation levels are known to be related to air pollution levels (higher elevations are more exposed to acidic deposition); 4) Climate change also influences foliar nutrition and metabolism simultaneously as was shown in red maple (Acer rubrum) trees exposed to soil warming with or without induced freeze-thaw cycles in a northern hardwood forest (Blagden et al, 2022); and 5) Rhizoctonia solani's damage to sugar beet increased in the presence of Leuconostoc mesenteroides as revealed by altered roots nutrient and metabolite levels in the infected roots (Majumdar et al, 2022). These authors suggested a common role of inorganic nutrients and primary metabolism in all host-plant fungal and bacterial pathogens besides the wellknown role of unique pathways and genes in the pathogens towards maintaining successful pathogenesis and the development of disease symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…According to these records, even when branches were sampled from within the mid-canopy area for a given study, but the distance from the top of the canopy varied more than two meters for the same trees, the concentrations of nutrients and metabolites in the foliage would be significantly different. Reported literature shows that under abiotic and biotic stress dilute acid-soluble inorganic nutrients and metabolites changed in concert in order to maintain homeostatic balance within cells (Minocha et al, 1997;Bubier et al, 2011;Schaberg et al, 2011;Ma et al, 2020;Mcdermot et al, 2020;Minocha et al, 2021;Blagden et al, 2022;Majumdar et al, 2022). Thus, the current practices of pooling foliar tissue (as described above) followed by drying and grinding before total inorganic nutrients analyses, though economical, are not the best if the goal is to advance our understanding of the collaborative role of nutrients alongside metabolites in maintaining homeostasis within the plant tissue under study.…”
Section: Introductionmentioning
confidence: 99%